Arabian Travellers, 1800–1950: An Analytical Bibliography. Issue 1 (2nd January 2016) - Reilly, Benjamin
Abstract: Western travelogue writing has long been a crucial source of information for scholars of the Arabian Peninsula, but nonetheless, this body of literature has not yet been studied comprehensively and systematically by a modern scholar. This article addresses that deficiency by collecting data on the nationality, routes travelled and intertextual citations of 91 authors active in Arabia from 1800 to 1950. The results of this study provide quantitative verification for several existing theories on Western travel writing in Arabia, including Edward Said's claim that 'Orientalism' was predominantly an Anglo-French project, and observations by Said, James Canton and others that European travellers had intimate ties with European imperialism. At the same time, this study challenges some existing arguments about Western travel writing in Arabia, especially claims by Alaine Hutson and others about the inherent unreliability of this corpus of sources.